2016
DOI: 10.1002/stem.2261
|View full text |Cite
|
Sign up to set email alerts
|

A Primitive Growth Factor, NME7AB, Is Sufficient to Induce Stable Naïve State Human Pluripotency; Reprogramming in This Novel Growth Factor Confers Superior Differentiation

Abstract: Scientists have generated human stem cells that in some respects mimic mouse na€ ıve cells, but their dependence on the addition of several extrinsic agents, and their propensity to develop abnormal karyotype calls into question their resemblance to a naturally occurring "na€ ıve" state in humans. Here, we report that a recombinant, truncated human NME7, referred to as NME7 AB here, induces a stable na€ ıve-like state in human embryonic stem cells and induced pluripotent stem cells without the use of inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 67 publications
1
17
0
Order By: Relevance
“…This study indicated that MTCH2 is important for elongated mitochondria which itself was sufficient for driving naïve-toprimed interconversion by altering histone deacetylation and nuclear gene reprogramming (Bahat et al, 2018). In addition, recent work has demonstrated that supplementation with a recombinant truncated human NME7 (NME7 AB ) is sufficient to induce a stable naïve-like state in hPSCs (Carter et al, 2016) associated with reactivation of mitochondrial function and stimulation of ATP production (O'Reilly et al, 2019).…”
Section: Mitochondrial Metabolismmentioning
confidence: 88%
“…This study indicated that MTCH2 is important for elongated mitochondria which itself was sufficient for driving naïve-toprimed interconversion by altering histone deacetylation and nuclear gene reprogramming (Bahat et al, 2018). In addition, recent work has demonstrated that supplementation with a recombinant truncated human NME7 (NME7 AB ) is sufficient to induce a stable naïve-like state in hPSCs (Carter et al, 2016) associated with reactivation of mitochondrial function and stimulation of ATP production (O'Reilly et al, 2019).…”
Section: Mitochondrial Metabolismmentioning
confidence: 88%
“…Smagghe et al 19 demonstrated through surface plasmon resonance that differential NME interaction with the extracellular domain of MUC1* is strictly dependent on the NME multimerization state. The updated mechanistic model 20 (Figure 1) suggests that early stem cells are able to secrete monomer NME7 that can bind to the extracellular domain of MUC1* and promotes growth and pluripotency. Hence, extracellular NME7 has an important role in maintenance of early stem cell in the naïve status.…”
Section: Extracellular Nme1 and Nme7 In Stem Cell Pluripotency Regulamentioning
confidence: 99%
“…Mechanistic model illustrating how NME7 and NME1 control pluripotency and differentiation in stem cells. Modified from Carter et al20 …”
mentioning
confidence: 99%
“…Several groups have developed various culture systems to revert EpiSC-like conventional human PSCs [41,48,107,119,[175][176][177][178][179][180][181][182][183] or derive de novo hESCs [41,107,178,184] to pluripotent states resembling the human preimplantation epiblast (Fig. 3).…”
Section: Conventional Mepisc-like Human Pscs Can Be Chemically Revertmentioning
confidence: 99%